Iodine sorption capacity of carbon fiber cloth materials and granular activated carbons - Gurin, I.V.; Sokolenko, V.I.; Vinokurov, E.I.; Sibileva, R.M.; Grigorova, T.G.; Grigorenko, M.A.; Kravtsov, Ya.V.; Kudin, D.V. (Вопросы атомной науки и техники, 2022)
The sorption capacity for iodine vapors of samples of carbon fiber cloth materials 31-3, 31-6, 35-1, 35-2, and KIPT 16-00 obtained at NSC KIPT, carbon fiber cloth materials of the Saut and Busofit brands and active granular carbons ISQ-3, SKT-3, and DGF-2 has been studied. The sorption capacity of carbon fiber cloth materials of series 31-6 and KIPT 16-00 is ~ 30% higher in comparison with Saut fiber cloth and ~ 4 times higher than the characteristics of active granular carbons SKT-3 and DGF-2 it has been shown. Досліджено сорбційну ємність по парам йоду зразків карбонових тканин 31-3, 31-6, 35-1, 35-2 і ХФТІ 16-00, отриманих в ННЦ ХФТІ, карбонових тканин марок Саут і Бусофіт і сортів активованого гранульованого вугілля ISQ-3, СКТ-3 і DGF-2. Показано, що сорбційна ємність у тканин серій 31-6 і ХФТІ 16-00 на ~ 30% вище в порівнянні з тканиною Саут і в ~ 4 рази перевищує характеристики сортів активованого гранульованого вугілля СКТ-3 та DGF-2. Исследована сорбционная емкость по парам йода образцов карбоновых тканей 31-3, 31-6, 35-1, 35-2 и ХФТИ 16-00, полученных в ННЦ ХФТИ, карбоновых тканей марок Саут и Бусофит и активированных гранулированных углей ISQ-3, СКТ-3 и DGF-2. Показано, что сорбционная емкость у тканей серий 31-6 и ХФТИ 16-00 на ~ 30% выше в сравнении с тканью Саут и в ~ 4 раза превышает характеристики активных гранулированных углей СКТ-3 и DGF-2.